Simulation of atomic displacements cascades in α-zirconium near β-Nb-20%Zr precipitate - P.E. Kapustin; M.Yu. Tikhonchev; R.T. Sibatov; V.V. Svetukhin (Results in Physics, 2019)
The evolution of atomic displacements cascades near the spherical binary precipitate Nb-20%Zr with the bcc lattice in the hcp α-Zr matrix was simulated using the method of molecular dynamics. The cascade is initiated by a 10 keV primary-knocked Zr atom at a distance ∼10 Å from the surface of spherical binary precipitate of radius ∼50 Å. The simulation results show that at the stage of the primary radiation damage, a change in the composition of the binary precipitate takes place. After passage of the cascade process, a considerable concentration of niobium in interstitial sites outside the precipitate is observed near the surface. The precipitate mitigates the propagation of atomic displacements cascade. In most cases, we observed cascade flow around the sphere accompanied by weak penetration into the precipitate structure. Index terms: Zr-Nb alloy, Atomic displacements cascade, Molecular dynamics, Simulation, Precipitate